Enhancing Reading Comprehension Through The Read Cover Remember Retell (RCRR) Method: An Experimental Study - Amirah; Dewi Kurniawati; Sri Suci Suryawati (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Based on the competency of national curriculum Merdeka, the students at second grade of SMA Negeri 10 OKU should be able to have reading comprehension on descriptive text. In this research, the researcher used Read Cover Remember Retell (RCRR) to teaching reading comprehension descriptive text at second grade of SMA negeri 10 OKU. This research aimed to find out the differences between the students taught by Read Cover Remember Retell (RCRR) strategy and the students taught without using Read Cover Remember Retell (RCRR) strategy in terms of reading comprehension descriptive text. Reading is crucial skill in learning English, as it facilitates students' overall language comprehension. This study aims to investigate the effectiveness of the Read Cover Remember Retell (RCRR) strategy in enhancing student' reading comprehension. The research was conducted with eleventh-grade at SMA Negeri 10 OKU, who are divided into to two groups: an experimental group taught using the RCRR strategy and a control group taught through conventional methods. A quantitative research method with an experimental design was employed, employing pre-test and post-test to measure improvement in reading comprehension. The findings provide valuable insight into the impact of the RCRR strategy on students' reading abilities, with implications for English language teaching practices.